Identification of novel candidate risk genes for myelomeningocele within the glucose homeostasis/oxidative stress and folate/one‐carbon metabolism networks. Issue 11 (22nd September 2020) - Hillman, Paul; Baker, Craig; Hebert, Luke; Brown, Michael; Hixson, James; Ashley‐Koch, Allison; Morrison, Alanna C.; Northrup, Hope; Au, Kit Sing
Abstract: Background: Neural tube defects (NTDs) are the second most common complex birth defect, yet, our understanding of the genetic contribution to their development remains incomplete. Two environmental factors associated with NTDs are Folate and One Carbon Metabolism (FOCM) and Glucose Homeostasis and Oxidative Stress (GHOS). Utilizing next‐generation sequencing of a large patient cohort, we identify novel candidate genes in these two networks to provide insights into NTD mechanisms. Methods: Exome sequencing (ES) was performed in 511 patients, born with myelomeningocele, divided between European American and Mexican American ethnicities. Healthy control data from the Genome Aggregation database were ethnically matched and used as controls. Rare, high fidelity, nonsynonymous predicted damaging missense, nonsense, or canonical splice site variants in independently generated candidate gene lists for FOCM and GHOS were identified. We used a gene‐based collapsing approach to quantify mutational burden in case and controls, with the control cohort estimated using cumulative allele frequencies assuming Hardy–Weinberg equilibrium. Results: We identified 45 of 837 genes in the FOCM network and 22 of 568 genes in the GHOS network as possible NTD risk genes with p  < 0.05. No nominally significant risk genes were shared between ethnicities. Using a novel approach to mutational burden we identify 55 novel NTD risk associations. Conclusions: We provide a means of utilizing large publicly available sequencing datasets as controls for sequencing projects examining rare disease. This approach confirmed existing risk genes for myelomeningocele and identified possible novel risk genes. Lastly, it suggests possible distinct genetic etiologies for this malformation between different ethnicities. Abstract : Neural tube defects (NTDs) are the second most common complex congenital birth defect and their genetic etiology remains incompletely understood. We utilize exome sequencing of 511 individuals with myelomeningocele and public database controls to identify candidate risk genes through mutational burden analysis. We present 64 candidate risk genes for NTDs, 56 of which are novel associations, and provide evidence of possible distinct molecular pathway roles for NTD risk in different ethnicities.